Parasitological evaluation of the neotropical otter Lontra longicaudis and the giant otter Pteronura brasiliensis: swimming in little-known waters before it is too late - Perin, Patricia Parreira; Leuchtenberger, Caroline; Furtado, Mariana Malzoni; Rodrigues, Livia de Almeida; Soresini, Grazielle; Foerster, Nathalie; Mourão, Guilherme; Oliveira, Wilson Junior; Mendonça, Talita Oliveira; Arias-Pacheco, Carmen Andrea; Loureiro, Fabiana Alves; Lux Hoppe, Estevam G. (Frontiers in Mammal Science, 2025)
IntroductionOtters are top predators in aquatic ecosystems and serve as indicators of environmental health. However, knowledge of the parasitology of South American species remains limited. This study investigated the endoparasitic fauna of two otter species in Brazil, the giant otter (Pteronura brasiliensis) and the Neotropical otter (Lontra longicaudis), to better understand their parasite diversity and the ecological interactions between hosts and parasites.MethodsBetween February 2020 and November 2021, a total of 42 fecal samples and four carcasses (three P. brasiliensis and one L. longicaudis) were collected in the Pantanal Ecoregion. Coproparasitological analyses were performed to detect parasite eggs and oocysts, while necropsies allowed for the recovery and identification of helminth specimens. Molecular sequencing of 18S and 28S rDNA was conducted for selected taxa, with sequences deposited in GenBank.ResultsCoproparasitological analysis revealed the presence of parasites in 81.6% of P. brasiliensis fecal samples, with digeneans, strongylid-type, and ascarid eggs identified. Cystoisospora sp. oocysts and strongylid-type eggs were detected in the L. longicaudis fecal samples. Necropsies recovered specimens of digeneans and cestodes, including Alaria clathrata, Cryptocotyle thapari, and Spirometra sp. spargana, with the first 18S and 28S rDNA sequences for A. clathrata and C. thapari deposited in GenBank.DiscussionThese findings advance our understanding of otter–parasite dynamics in Neotropical wetlands and highlight the value of parasitological monitoring as part of conservation strategies for threatened wildlife.